Effects of N placement, carbon distribution and temperature on N2O emissions in clay loam and loamy sand soils. (7th March 2013) - Xue, Y.; van, H. M.; Schindelbeck, R. R.; Moebius‐Clune, B. N.; Melkonian, J. J.; Graham, C.; Yang, P.
Abstract Changes in the profile distribution of soil C stocks for conventional versus no‐tillage can affect N2O losses. Uncertainty remains whether deep N placement into a wetter layer in humid areas would affect N2O losses. This study evaluated the effects of soil carbon profile distribution (inverted, normal), depth of nitrogen placement (5 cm, 15 cm), temperature (10, 20 and 30 °C) and soil texture (clay loam, loamy sand) on N2O emissions from soil cores in a 216‐h incubation after simulated rainfall. N2O losses were larger from the clay loam than from the loamy sand, and cumulative N2O emissions from the inverted profile, with greater C levels at depth, were more than those from the profile with more C near the upper surface. Cumulative N2O losses from the inverted clay loam profile with deep N placement (1.16 mg N per kg dry soil; 0.71% of applied N) on average were almost double those in the loamy sand (0.62 mg N per kg dry soil; 0.42%). The smallest N2O losses were measured from the profiles with more C close to the upper surface with a shallow placement of N for the clay loam (0.19 mg N per kg dry soil; 0.12%) and loamy sand (0.33 mg N per kg dry soil; 0.23%). An exponential relationship between N2O fluxes and temperature was measured. We conclude that large N2O losses may occur under the combination of greater soil C content at deeper layers (ploughed soils) and moist profiles after N application (humid regions). Deep N placement appears to aggravate rather than ameliorate these concerns.